Irradiation stability and induced ferromagnetism in a nanocrystalline CoCrCuFeNi highly-concentrated alloy. Issue 48 (3rd December 2021) - Tunes, Matheus A.; Greaves, Graeme; Rack, Philip D.; Boldman, Walker L.; Schön, Cláudio G.; Pogatscher, Stefan; Maloy, Stuart A.; Zhang, Yanwen; El-Atwani, Osman
Abstract : Thermodynamic instabilities driven by temperature and irradiation in a nanocrystalline highly-concentrated alloy promote the nucleation and growth of FeCo-rich "nanomagnets". Abstract : In the field of radiation damage of crystalline solids, new highly-concentrated alloys (HCAs) are now considered to be suitable candidate materials for next generation fission/fusion reactors due to recently recorded outstanding radiation tolerance. Despite the preliminarily reported extraordinary properties, the mechanisms of degradation, phase instabilities and decomposition of HCAs are still largely unexplored fields of research. Herein, we investigate the response of a nanocrystalline CoCrCuFeNi HCA to thermal annealing and heavy ion irradiation in the temperature range from 293 to 773 K with the objective to analyze the stability of the nanocrystalline HCA in extreme conditions. The results led to the identification of two regimes of response to irradiation: (i) in which the alloy was observed to be tolerant under extreme irradiation conditions and (ii) in which the alloy is subject to matrix phase instabilities. The formation of FeCo monodomain nanoparticles under these conditions is also reported and a differential phase contrast study in the analytical electron-microscope is carried out to qualitatively probe its magnetic properties.